2015
DOI: 10.3759/tropics.24.23
|View full text |Cite
|
Sign up to set email alerts
|

Neighboring tree effect on the survival and growth of <i>Shorea johorensis</i> under a line planting system in a Bornean dipterocarp forest

Abstract: In Indonesia, in recent years, line planting of valuable Shorea species has taken place on logged forest to maintain the timber yield. However, there exists scant information about the effectiveness of such a method. Neighboring trees along the planting lines affect the planted trees. We assessed the survival, growth, and crown exposure of the planted trees to evaluate the effect of neighboring trees in three 1 ha-monitoring plots, in which Shorea johorensis seedlings had been planted at a 5-m spacing along fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…The implementation of Sustainable Forest Management (SFM) in PBPH can expedite the ecological restoration of degraded forests, due to its 27-year production cycle compared to the 30-year of logging rotation (Hilwan et al 2012). A study by Inada et al (2015) has shown an increase in the number of trees in the ex-logging areas after 11 years of Shorea spp. plantation.…”
Section: Potential Carbon Benefits From Shorea Leprosula Silin Vegeta...mentioning
confidence: 99%
“…The implementation of Sustainable Forest Management (SFM) in PBPH can expedite the ecological restoration of degraded forests, due to its 27-year production cycle compared to the 30-year of logging rotation (Hilwan et al 2012). A study by Inada et al (2015) has shown an increase in the number of trees in the ex-logging areas after 11 years of Shorea spp. plantation.…”
Section: Potential Carbon Benefits From Shorea Leprosula Silin Vegeta...mentioning
confidence: 99%
“…Untuk nilai Indeks Kemerataan (e) tergolong hampir merata pada semua tingkat pertumbuhan dengan nilai e antara 0,76 -0,95 (Karmilasanti & Fajri, 2020) (Panjaitan et al, 2012). Kondisi serupa juga ditemukan pada hutan produksi di Kalimantan Tengah yang dijumpai Shorea johorensis (Inada et al, 2015). Penelitian yang dilakukan di Taman Nasional Gunung Leuser, Aceh, juga menemukan bahwa Shorea johorensis masih tumbuh baik di sana (Harnelly et al, 2018).…”
Section: B Komposisi Vegetasi Tingkat Pancangunclassified
“…The medium-term silvicultural results of Silin, as applied in PT. Sari Bumi Kusuma, are impressive, with seedling survival rates of about 70% and rates of stem diameter increments consistently averaging about 2 cm per annum, based on 10-14 years of post-planting data from permanent sample plots [1,2]. At first glance, TPTJ seems easy to implement in the field and does not cause many problems.…”
Section: Introductionmentioning
confidence: 99%